Identification of an AXL kinase inhibitor in triple‐negative breast cancer by structure‐based virtual screening and bioactivity test. (29th October 2021) - Li, Pei; Niu, Yuzhen; Li, Shuyan; Zu, Xuyu; Xiao, Maoyu; Yin, Liyang; Feng, Jianbo; He, Jun; Shen, Yingying
Abstract: Breast cancer is a malignant tumor that occurs in the glandular epithelium of the breast, and more than 15% of the patients are triple‐negative breast cancer (TNBC). Therefore, finding new targets and targeted therapeutic drugs for TNBC is urgent. Overexpression of the AXL is associated with motility and invasiveness of the TNBC cells, which is a potential target for breast cancer therapy. A compound Y041‐5921 (IC50  = 6.069 μm for AXL kinase and IC50  = 4.1 μm for MDA‐MB‐231 cell line) was identified through structure‐based virtual screening and bioassay test for the first time. The compound Y041‐5921 could significantly inhibit the proliferation and invasion of the TNBC cells and the toxicity of Y041‐5921 to normal immortalized breast epithelial cells was far lower than that of commonly used clinical chemotherapy drugs. Besides, it also had well inhibitory effect on the proliferation of many other malignant tumor cell lines (the IC50  value are 10.0 m, 7.1 m, 10.3 m, 11.4 m and 5.8 m for U251 cell, COLO cell, PC‐9 cell, CAKI‐1 cell and MG63 cell, respectively). The interaction mechanism between Y041‐5921 and AXL was studied by molecular dynamics (MD) simulations and binding free energy calculation, and the key residues whose energy contribution mainly comes from non‐polar solvation interaction (such as Ala565, Lys567, Met598, Leu620, Pro621, Met623, Lys624, Arg676, Asn677 and Met679) were identified. The small molecule inhibitors Y041‐5921 targeting AXL reported in this work will lay a foundation and provide a theoretical basis for the development of the TNBC. Abstract : (1) The structure‐based virtual screening and bioassay test were used to identify a compound Y041‐5921 (IC50  = 6.069 μm for AXL kinase and IC50  = 4.1 μm for MDA‐MB‐231 cell line). (2) Y041‐5921 could significantly inhibit the proliferation and invasion of the TNBC cells and the toxicity of Y041‐5921 to normal immortalized breast epithelial cells was far lower than that of commonly used clinical chemotherapy drugs. (3) The key residues whose energy contribution mainly comes from non‐polar solvation interaction (such as Ala565, Lys567, Met598, Leu620, Pro621, Met623, Lys624, Arg676, Asn677 and Met679) were identified.